PROSES PERUMUSAN KEBIJAKAN DESA OLEH BADAN PERMUSYAWARATAN DESA (BPD) DI DESA SEDEDAP KECAMATAN PULAU TIGA KABUPATEN NATUNA - Januar Ependi E.01108043 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Writing this article is intended to determine how the process of policy formulation by the village Village Consultative Body (BPD), because it is still found fonomena which identifies the lack Village Consultative Body (BPD) is formulating a policy. This research is a descriptive research using qualitative methods. The research was conducted at the office of the Village Consultative Body (BPD) Sededap District Three District Natuna Island. The policy formulation process is theoretically through several stages, the identification and understanding of issues, agenda setting, formulation of public policy issues, and policy design. Dar result of this study is on the identification and understanding of the issue is still not done, at this stage of the preparation of the agenda has been done but has not indicated a maximum in terms of quality and quantity, in the formulation of public policy issues is not done, as well as at the policy design stage is not done. Education, experience possessed Consultative Agency (BPD) is still low. Researchers concluded BPD members must perform the process steps for the formulation of policy formulation processes accomplish better.Keywords: Policy Formulation, Identification and Problem Awareness, Preparation of Agenda, Formulation of Public Policy Issues, Policy Design